Enhancing Maritime ESP Reading Comprehension through Kahoot-Based Gamification: A Mixed-Methods Study among Maritime Cadets in Indonesia - Nindy Nource Ganap; Tini Mogea; Ceisy Nita Wuntu (Austronesian: Journal of Language Science & Literature, 2026)
The integration of digital technology into English for Specific Purposes (ESP) instruction has become increasingly important in vocational and professional education. In maritime education, the ability to comprehend technical texts and master specialized vocabulary is essential for effective communication and operational safety. However, many maritime cadets continue to experience difficulties in reading comprehension due to limited vocabulary mastery, low learning motivation, and the predominance of conventional teacher-centered instructional approaches. This study investigated the effectiveness of Kahoot-based gamification in improving maritime cadets’ reading comprehension and technical vocabulary mastery in ESP classes. Employing a mixed-methods sequential explanatory design, the study involved 23 third-semester cadets from the Nautical Study Program at North Sulawesi Maritime Polytechnic. Quantitative data were collected through pre-tests, post-tests, and questionnaires, while qualitative data were obtained through classroom observations and semi-structured interviews. Statistical analysis revealed significant improvements in reading comprehension and maritime vocabulary mastery across three intervention sessions, with all paired-sample t-tests yielding significance levels below .001. Questionnaire results indicated highly positive perceptions regarding the ease of use, usefulness, and motivational impact of Kahoot. Qualitative findings further demonstrated increased engagement, reduced language anxiety, enhanced metacognitive awareness, and stronger peer collaboration. The findings suggest that Kahoot-based gamification provides an effective pedagogical approach for improving ESP reading instruction in maritime education. The study contributes to the growing literature on gamification in vocational ESP contexts and offers practical implications for technology-enhanced maritime language instruction.